Do foreign aid triggers economic growth in Chad? A time series analysis - Dervis Kirikkaleli; Ibrahim Adeshola; Tomiwa Sunday Adebayo; Abraham Ayobamiji Awosusi (Future Business Journal, 2021)
This study explores the nexus between foreign aid and Chad's economic growth. Empirical evidence is based on annual data from 1982 to 2018. The study used ARDL, FMOLS, and DOLS techniques to establish interconnection among the economic indicators. Subsequently, the study utilized the wavelet coherence technique to capture causality and correlation between economic growth and the independent variables. One of the wavelet approach's uniqueness is that it shows the pattern and behavior of the variables used, including the different time horizons. Thus, we explore the dynamic influence of gross capital formation, foreign aid, import, and export on Chad's economic growth. The result of the ARDL long-run estimates reveals that gross capital formation and foreign aid exert insignificant impact on GDP growth. However, exports and imports exert a positive and significant impact on GDP growth. Furthermore, the global financial crisis has a negative and significant impact on the economy of Chad. The outcomes of the wavelet coherence test provide supportive evidence for the ARDL long-run outcomes. Hence, we suggested that substantial macroeconomic reforms and economic liberalization initiatives will help in the dissemination of information and promote domestic investment and importation of high-tech goods.
Keywords: 650; ARDL; DOLS; Economic growth; FMOLS; Foreign Aid; Wavelet coherence